Philosophy, Mythology and an African Cosmological System (Global Journal of Human-Social Science, 2012)
There is a tendency by some scholars, especially those professional African philosophers who belong to the analytic school of African philosophy, to deny any relationship between philosophy, myth and cosmology. Their denial is based on their characterisation of philosophy as a rational and critical inquiry, while myth and cosmology are taken by them as belonging to the realm of stories, folktales etc. created by so-called primitive or traditional society to satisfy some emotional and instinctual need. Hence, they conclude that the concepts are unrelated. However, I shall argue that there is a deeper relationship between them than it is acknowledged since myth and cosmology constitute the raw material for philosophy. Again, both concepts offer a perspective for an interpretation of the world and the mysteries and phenomena of existence in general.
Keywords: Philosophy; Mythology Cosmological System